2014
DOI: 10.1016/j.mri.2014.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Rapid acquisition technique for MR elastography of the liver

Abstract: Magnetic Resonance Elastography (MRE) of the liver is a novel noninvasive clinical diagnostic tool to stage fibrosis based on measured stiffness. The purpose of this study is to design, evaluate and validate a rapid MRE acquisition technique for noninvasively quantitating liver stiffness which reduces by half the scan time, thereby decreasing image registration errors between four MRE phase offsets. In vivo liver MRE was performed on 16 healthy volunteers and 14 patients with biopsy-proven liver fibrosis using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 34 publications
(36 reference statements)
0
47
0
Order By: Relevance
“…This study also showed that MRE could discriminate patients with moderate and severe fibrosis (grades 24) from those with mild fibrosis (sensitivity, 86%; specificity, 85%). Several studies show that MRE is more reliable for staging hepatic fibrosis compared to DWI and conventional MRI, with a powerful combination of sensitivity, specificity, likelihood ratios, diagnostic odds ratio, and area under the summary receiver operating characteristic curve values [51,[53][54][55] (Table 2). MRE can be easily added to standard abdominal MRI protocols, promising value added in staging liver cirrhosis.…”
Section: Mrimentioning
confidence: 99%
“…This study also showed that MRE could discriminate patients with moderate and severe fibrosis (grades 24) from those with mild fibrosis (sensitivity, 86%; specificity, 85%). Several studies show that MRE is more reliable for staging hepatic fibrosis compared to DWI and conventional MRI, with a powerful combination of sensitivity, specificity, likelihood ratios, diagnostic odds ratio, and area under the summary receiver operating characteristic curve values [51,[53][54][55] (Table 2). MRE can be easily added to standard abdominal MRI protocols, promising value added in staging liver cirrhosis.…”
Section: Mrimentioning
confidence: 99%
“…Magnetic resonance elastography (MRE) is a noninvasive technique to estimate stiffness of soft tissues (9-15) and is currently a clinical diagnostic tool to stage liver fibrosis (16-20). To date there are few studies to evaluate the feasibility of in-vivo pancreatic MRE (21-24).…”
Section: Introductionmentioning
confidence: 99%
“…Limitations seen with similar studies including placement of the passive driver on the patient, diff erences in body habitus aff ecting contact area, as well as the subtle diff erences in the spatial stiff ness maps due to diff erences in breath hold apply to both techniques (i.e., 3D and 2D) ( 27 ).…”
Section: Liver © 2016 By the American College Of Gastroenterologymentioning
confidence: 99%